Mechanism study of exercise intervention on circadian disruption in Alzheimer’s disease - Zhang, Mingzheng; Shi, Lei; Meng, Xiangqi; Dong, Yahong; Sun, Yinjie; Qian, Qiheng; Jin, Qiguan (Frontiers in Neuroscience, 2025)
Alzheimer’s disease (AD) induces profound circadian disruption—characterized by suprachiasmatic nucleus (SCN) degeneration, Aβ and tau pathology, and aberrant melatonin secretion which results in fragmented sleep–wake cycles and cognitive decline. Emerging evidence indicates that exercise significantly ameliorates these circadian rhythm and sleep–wake disturbances through multiple mechanisms. Specifically, exercise accelerates the removal of Aβ and tau by activating autophagy–lysosomal degradation and glymphatic clearance, thereby reducing the neuropathological burden. Furthermore, exercise also upregulates neuroprotective pathways and strengthens the amplitude and phase stability of core clock gene oscillations, which in turn restores robust melatonin rhythmicity and SCN function. Collectively, these effects break the vicious cycle between AD pathology and circadian disruption, stabilizing circadian homeostasis and improving cognitive function. These mechanistic insights highlight exercise as a robust non-pharmacological chronotherapeutic strategy for ameliorating circadian disruption in AD. These insights support the development of personalized, chronotype-tailored exercise interventions to resynchronize circadian rhythms and ultimately improve sleep quality and cognitive function in patients with AD.